Abutment coating with diamond-like-carbon films to reduce implant-abutment bacterial leakage - Cardoso, Mayra; Sangalli, Jorgiana [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Ferreira, Leandro Lameirão; da Silva Sobrinho, Argemiro Soares; Nogueira, Lafayette [UNESP] (Journal of Periodontology, 2015)
Backgroud: The influence of diamond-like-carbon (DLC) films on bacterial leakage through the interface between abutments and dental implants of external hexagon (EH) and internal hexagon (IH) was evaluated. Film deposition was performed by PECVD (Plasma Enhanced Chemical Vapor Deposition). Sets of implants and abutments (N=180, n=30) were divided according to the connection design and the treatment of the abutment base: (1) no treatment (control); (2) DLC film deposition, and (3) Ag-DLC film deposition. Under sterile conditions, 1 µL of Enterococcus faecalis was inoculated inside the implants, and abutments were tightened. The sets were tested for immediate external contamination, suspended in test tubes containing sterile culture broth, and followed-up for five days. Turbidity of the broth indicated bacterial leakage. At the end of the period, the abutments were removed and the internal content of the implants was collected with paper points and plated in Petri dishes. They were incubated for 24 h for bacterial viability assessment and colony-forming unit (CFU) counting. Bacterial leakage was analyzed by Chi-square and Fisher exact tests (α=5%). The percentage of bacterial leakage was 16.09% for EH implants and 80.71% for IH implants (P<0.0001). The bacterial load was higher inside these implants (P=0.000). The type of implant significantly influenced the results (P=0.000), whereas the films did not (P=0.487). We concluded that: (1) IH implants showed a higher frequency of bacterial leakage and (2) the DLC and Ag-DLC films did not significantly reduce the frequency of bacterial leakage and bacteria load inside the implants.
Keywords: Bacterial load; Enterococcus faecalis; Dental implants; Microbial viability; Microbiology; Plasma gases